(untitled) (Academic journal Industrial Machine Building Civil Engineering, 2019)
The problems of society informational support, which demand the creation of modern information management systems for different objects were considered. Particular attention was paid to the detailed description and analysis of existing services for keeping records of scientific activity in higher educational institutions. The necessity of module creating for management the scientific and technical activities, which will allow to optimize the procedure for conducting reports on scientific, technical and innovative activities, to expand the possibilities for the results analysis, to ensure transparency and objectivity in the procedure of evaluating the teachers’ activities, was revealed and explained. The developed sections of the technical enquiry were given. On the basis of the conducted research the software implemented module for management the scientific and technical activity of the department.